Analisis preferensi pilihan jenis pekerjaan di Bangka Belitung - Basorudin, Muhammad; Humairo, Nadia (Jurnal Paradigma Ekonomika, 2019)
Preference of job choice is a study to look the pattern of the economy in a region. This study is also used as an alternative measure to look at the economy structure in that region other than GDP distribution. The purpose of this study is to determine the preferences of the working age population in choosing the type of employment based on the number of working hours and gender. By using logistic multinomial regression model, the variables used are the categorical independent variables ie gender (male and female) and working hours (0-34 hours and 35+ hours per week) and the nominal response variable ie primary jobs (primary, secondary, and tertiary). The results showed that variables the number of working hours and gender significantly affect the main types of primary jobs.